Kewenangan Pengadilan Dalam Pemulihan Hak Konsumen Jasa Layanan Umroh (Studi terhadap Putusan Nomor 52/Pdt.G/2019/PN.Dpk) - Tribuana Chris Shinta; Anna Maria Tri Anggraini (Fakultas Hukum Universitas Tarumanagara, 2020)
In Article 9 Government Regulation of the Republic of Indonesia Number 79 of 2012 concerning the Implementation of Law Number 13 of 2018 concerning the Implementation of Hajj, states the meaning of Umrah is Umrah which is performed outside the Hajj season. The Organization of Umrah Travel is aimed at providing guidance, service and protection to the Congregation, so that the Congregation can perform their worship in accordance with the provisions of the Sharia based on Article 3 of the Minister of Religion Regulation of the Republic of Indonesia Number 8 of 2008 concerning the organization of Umrah pilgrimage. Protection of consumers is seen as increasingly important, With the development of science and technology most consumers are affected. Therefore, consumers must be given legal protection because the interests of consumers are important things that must be considered and given a solution, especially in Indonesia. The authority describes the right and obligation to do and not do something. Authority is divided into two, namely absolute authority and relative authority. Analysis results show in the court decision number 52 / Pdt.G / 2019 / PN. But the law enforcement is still not effective in Indonesia. The method used in this research is to use prescriptive analysis, to find the truth of coherence and provide arguments for the results carried out. This study aims to increase supervision and regular guidance of Umrah Travel Agents, as well as tougher to give permission to Umrah Travel Agencies so that no more consumers feel disadvantaged.